Rancang Bangun Mesin Pengurai Gumpalan Tepung Tapioka Dengan Penggerak Motor Listrik 1 HP - Alfauzi, Abdul Syukur; Nugroho, Wahyu Isti; Mudjijanto, Mudjijanto; Abidin, Zaenal; Norfitayana, Fredy (Journal of Mechanical Engineering and Applied Technology, 2023)
Almost all tapioca flour manufacturers at the home S.M.E. level, particularly in the Sidomukti district of Pati, Central Java, manufacture tapioca flour only to the final stage as a lump of tapioca flour. The results of this S.M.E. cannot be directly marketed to consumers because it must go through a process again so that the flour is smooth, so S.M.E. will sell tapioca flour lumps in the factory to be processed into ready flour to be marketed, resulting in lower profits for S.M.E.s producing tapioca flour and because there is no machine to decompose tapioca flour clumps for household production scale. Machine for breaking lumps of tapioca flour, this 1-horsepower electric motor drive is designed to alleviate challenges in S.M.E.s. This machine has a 50kg/h capacity and uses a 1:5 rotation ratio transmission mechanism via pulleys and a belt. When the electric motor is turned on, pulley one on the motor will rotate and move pulley two on the shaft, which then drives the mixer (stirrer), which will break down the flour that is put through the hopper and immediately filtered by mess, which has a hole size of 0.5 mm, and flour will come out through the output hopper that is under the body. This machine is semi-automatically operated by pushing ON to turn on and OFF to turn off. This machine will perform as intended